Synthetic hydrogel nanoparticles for sepsis therapy - Hiroyuki Koide (Nature Portfolio, 2021)
Sepsis caused by the release of inflammatory mediators into the blood is a life threatening disease. Here, the authors report on the development of hydrogel nanoparticles for the capture and neutralisation of histones, major inflammatory mediators, and demonstrate sepsis treatment in a murine model.